RANCANGAN MEDIA PEMBELAJARAN PROGRAM LINEAR BERBASIS ANDROID MENGGUNAKAN PROGRAM LECTORA INSPIRE DI SEKOLAH MENENGAH ATAS - Yeni Dian Utami; Edy Yusmin; Ade Mirza (UNIVERSITAS TANJUNGPURA, 2022)
This study aims to produce an Android-based linear programming learning media using Lectora Inspire that is feasible and effective for use in the learning process. This research is motivated by learning that must go hand in hand with technological developments and students have other learning resources not necessarily from the teacher, namely by using Android. This research is a research and development using a 4D model. The stages used are only up to Development. The subjects in this study were three material experts, three media experts and the responden of 24 students of grade XI. The object of the study is the product of the Android-based linear program learning media design using the Lectora Inspire program. The data collection instrument in this study to use a questionnaire. The result showed that the product made obtained an average score of 4.69 in the very eligible category based on material experts and an average score of 4.33 in the very eligible category based on media esperts Meanwhile, for students responses, obtained an average score of 4.19 was obtained in the eligible category. So the Android-based linear programming learning media using Lectora Inspire is feasible to use.